Judith Hermann’s early stories – description of subjective sensitivies or a critical diagnosis of the time? - Arnaudova, Svetlana (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2024)
After the publication of Judith Hermann’s first volume of short stories, Summerhouse Later, literary criticism attested to Hermann’s characters’ aloofness and lack of ambition and initiative and placed them in a Berlin artistic scene that lives without major goals or projects and is hardly touched by the outside world. The article puts forward the thesis that this reception of Hermann’s early texts has changed over time and that today one can place her stories in a broader political and historical context. Against the background of advancing globalization, Hermann’s texts prove to be a subtle diagnosis of the times and a criticism of the negative consequences of globalization.